Is Plaque Rupture Always Responsible in Acute Coronary Syndrome? - Putrika Prastuti Ratna Gharini (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2019)
The majority cause of myocardial infarction is the atherothrombotic event, mainly cause by plaque rupture. Since the 20th century, it was found that the plaque rupture was not the solely condition responsible for the acute coronary syndrome. With the invention of more sensitive myocardial biomarker, a series of guideline was written as guideline for the definition of myocardial infarction. This review discuss about the consensus in the Universal Definition of Myocardial Infarction.